Phosphorescent Molecularly Doped Light-Emitting Diodes with Blended Polymer Host and Wide Emission Spectra - Jun Wang; Jun Gou; Weizhi Li (The Scientific World Journal)
Stable green light emission and high efficiency organic devices with three polymer layers were fabricated using bis[2-(4′-tert-butylphenyl)-1-phenyl-1H-benzoimidazole-N,C2′] iridium(III) (acetylacetonate) doped in blended host materials. The 1 wt% doping concentration showed maximum luminance of 7841 cd/cm2 at 25.6 V and maximum current efficiency of 9.95 cd/A at 17.2 V. The electroluminescence spectra of devices indicated two main peaks at 522 nm and 554 nm coming from phosphor dye and a full width at half maximum (FWHM) of 116 nm. The characteristics of using blended host, doping iridium complex, emission spectrum, and power efficiency of organic devices were investigated.